(untitled) (PROCEEDING: The Annual International Conference on Islamic Education, 2019)
introduction of group B image media in RA. Nyai Munifah Kraton Pasuruan was needed in this study because it helped introduce children to word for word according to the enhanced spelling. Besides that this research uses Descriptive Qualitative Research Method that uses data collection techniques used is observation, while the understanding of qualitative research is research on descriptive research and tends to use analysis, process and meaning (subject perspective) more highlighted in qualitative research. the theoretical foundation is used as a guide so that the focus of research is in accordance with the facts in the field In addition, this theoretical basis is also useful to provide a general description of the background of the research and as an explanation for the results of the research. Research subjects are very necessary because the subjects of the research are student name data as the variable under study. The subjects in the study were children of group B. RA Nyai Munifah at Kraton Pasuruan. The object of this research is the improvement of distinguishing an image in RA. The munifah is at Kraton Pasuruan. Data collection techniques used are questionnaires, interviews, observations, documentation, tests or tests (tests), and so forth. Data analysis techniques were carried out in qualitative and quantitative descriptive. The success criteria in this study if the skill to distinguish children has reached 80% with very good criteria. The results showed an increase in cognitive abilities in terms of reading in group B in RA. Nyai munifah at Kraton Pasuruan. From the results of the study with interviews with parents and accompanying teachers of the image media The steps taken to determine the increase in cognitive ability to read are as follows: 1) Determining learning objectives 2) Choosing learning material 3) Determining topics that students will actively learn 4) Determine appropriate learning activities for these topics 5) Develop learning methods to stimulate children’s creativity and ways of thinking.